2016
DOI: 10.1177/1071100716665113
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative PROMIS Scores Predict Postoperative Success in Foot and Ankle Patients

Abstract: Level II, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
222
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 199 publications
(232 citation statements)
references
References 18 publications
(32 reference statements)
10
222
0
Order By: Relevance
“…We then performed receiver operator characteristic analysis to determine whether preoperative PROMIS scores could predict the likelihood that a patient would obtain a clinically meaningful benefit from foot and ankle surgery. 4 We found that a patient with a PROMIS physical function T score above 42, for example, has a 94% chance of not experiencing a minimal clinically important difference in function after surgery. Similarly, a patient with a preoperative pain T score below 55 has a 95% chance of not obtaining a meaningful benefit in terms of pain interference.…”
Section: Patient-reported Outcomes -Are They Living Up To Their Potenmentioning
confidence: 74%
“…We then performed receiver operator characteristic analysis to determine whether preoperative PROMIS scores could predict the likelihood that a patient would obtain a clinically meaningful benefit from foot and ankle surgery. 4 We found that a patient with a PROMIS physical function T score above 42, for example, has a 94% chance of not experiencing a minimal clinically important difference in function after surgery. Similarly, a patient with a preoperative pain T score below 55 has a 95% chance of not obtaining a meaningful benefit in terms of pain interference.…”
Section: Patient-reported Outcomes -Are They Living Up To Their Potenmentioning
confidence: 74%
“…We recommend that PROs should be collected at baseline, throughout the inpatient stay, and after hospital discharge. 4. At the current time we recommend that PROs should be collected using the QoR-15 during the immediate postoperative period (at a minimum on postoperative day #1 and at discharge) and either the WHODAS 2.0, or PROMIS at 30 days and 90 days after surgery.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…3 PROs in patients undergoing ankle surgery and found that patients with low preoperative physical function and high pain interference experienced superior outcomes after surgery whereas patients with less profound perturbation in preoperative physical function and pain experienced a smaller benefit. 4 Accordingly, use of PROs within the perioperative setting has the potential to enhance shared decision making between surgeons and patients regarding treatment options that can be specific to the type of surgery that they are planning.…”
Section: Introduction: the Role Of Patient Reported Outcomes In Enhanmentioning
confidence: 99%
“…For example, preoperative instrument scores have also been used to determine which patients are best suited for surgery. 37,38 More specifically, data suggest SNOT-22 scores of at least 20 in those who have failed maximal medical therapy indicate sufficient symptom impact to warrant endoscopic sinus surgery; accordingly, an international expert panel endorsed this threshold value as one of three operative indications on which their group could achieve consensus. 38 In patients with sensorineural hearing loss, randomized clinical trial data suggest that those with Inner EAR scores of 27 (95% CI: 25-28) improve, on average, to a score of 65 when amplification devices are utilized.…”
Section: Implications For Practicementioning
confidence: 99%